ANALISIS FAKTOR YANG MEMPENGARUHI KADAR GULA DARAH (KGD) PADA PASIEN DM TIPE II YANG BEROBAT KE RSU SEMBIRING TAHUN 2021 - Ruth Sthephanie Simanjuntak (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
ABSTRACT Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action, or both (American Diabetes Association (ADA) 2018). The mortality rate due to DM worldwide reached 1.5 million people in 2012, in 2014 the prevalence of DM sufferers was estimated at 9% of the total world population (WHO, 2015). The study aims to analyze the factors that affect blood sugar levels (KGD) of type II DM patients who are being treated at the Sembiring Hospital in 2021. This research was a quantitative research that analytic observational with a case contro research design. The population was all type II DM patients. The control population was a patient who was not diagnosed with type II diabetes who was carrying out an examination at the Delitua Health Center, a sample of 54 people. With a ratio of 1:1, namely 54 cases and 54 controls. Data analysis was performed using univariate analysis, bivariate analysis with chi square and multivariate with logistic regression test at α= 0.05. The results showed that there was an effect of stress factors (0.001), lifestyle (0.004), body weight (0.011), medication adherence (0.032) on blood sugar levels of type II DM patients. Of the four variables that predominantly affect the blood sugar levels of type II DM patients is the stress factor. The conclusion is that there is an effect of stress, lifestyle, body weight and medication adherence to blood sugar levels of type II DM patients. It is recommended for type II DM patients to control DM disease and to check blood sugar levels regularly at least once or 2 months.